2021
DOI: 10.1108/ijis-12-2020-0277
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and barriers of new product development success: evidence from an emerging economy setting country-Turkey

Abstract: Purpose Context characteristics of emerging economies differ significantly from those in developed economies. Considering this substantial difference, this study aims to identify the drivers and barriers for new product development (NPD) success in the context of an emerging economy by drawing on the resource-based view. Design/methodology/approach Data was collected from firms in different sectors in the Aegean Region of Turkey using the Wageningen Innovation Assessment Tool. Of 189 responses, 94 fit the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…The research presented in this paper is consistent with existing literature, which emphasizes the crucial role of equity capital in promoting innovation activity among SMEs (Błach et al, 2020;Carpenter and Petersen, 2002;Duran et al, 2022;Eldridge et al, 2021;Kortum and Lerner, 2000). The analysis, moreover, revealed a particularly strong association with…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…The research presented in this paper is consistent with existing literature, which emphasizes the crucial role of equity capital in promoting innovation activity among SMEs (Błach et al, 2020;Carpenter and Petersen, 2002;Duran et al, 2022;Eldridge et al, 2021;Kortum and Lerner, 2000). The analysis, moreover, revealed a particularly strong association with…”
Section: Introductionsupporting
confidence: 90%
“…SMEs can acquire the necessary capital via two pathways: debt financing and/ or equity financing. Previous literature has demonstrated that equity financing can be valuable for SMEs (Carpenter and Petersen, 2002), particularly in the context of funding innovation (Duran et al, 2022;Kortum and Lerner, 2000).…”
Section: Previous Literaturementioning
confidence: 99%
“…The review of 56 quantitative articles found the following specific areas of performance: new product development performance (Mu, 2017;Park and Kim, 2013;Pavlou and El Sawy, 2011) and new product success (Zhang and Wu, 2017). New Product Success (NPS) is the exploitation stage of the new product development process and covers the commercialization phase (Duran et al, 2021). Borah et al (2021) defined NPS as "new product abilities to meet customer needs, gain market popularity, and generate profit" (Borah et al, 2021;Hultink et al, 2000;Ledwith and O'Dwyer, 2008).…”
Section: The Measurement Of Dcsmentioning
confidence: 99%
“…It also focuses on how this innovation develops quickly, massively, and effectively by stakeholders. The innovation process is well performed by understanding the factors that facilitate and hinder its development (Garrigos, 2020;Sucha et al 2021;Duran et al 2021). According to Tiina and Leena (2015), the components promoting or facilitating this innovation are more common than the inhibiting one which also become the focus of this study.…”
Section: Introductionmentioning
confidence: 96%